There are a few ways to solve system of equations. You could use the matrix approach but I am going to use elimination.
x − 2y = 14
x + 3y = 9
First I am going to times x + 3y = 9 by -1, which will turn the x into -x and allow use to eliminate the x and solve for y.
-1(x + 3y) = 9(-1)
-x - 3y = -9
Ok now that we have our new equation, lets use that.
x − 2y = 14
-x - 3y = -9
-------------------
0 -5y = 5
Get ride of the 0
-5y = 5
Divide out the -5
-5y / -5 = 5 / -5
y = - 1
Now that we have found y = -1 insert -1 in the equation x + 3y = 9 to find x
x + 3y = 9
x + 3(-1) = 9
x - 3 = 9
x = 9 + 3
x = 12
x = 12
y = -1
(x, y) = (12, -1) = c